2022
DOI: 10.1038/s41598-022-14657-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear mode saturation in a U-shaped micro-resonator

Abstract: Saturation is an intriguing phenomenon that has captured the attention of scientists since the time of Froude when he reported it for ship motion in the mid of the nineteenth century. This work presents the demonstration and a comprehensive study of the nonlinear saturation phenomenon on a compound micromachined structure of U-shape (micro portal frame). The frame is designed and fabricated as a multi-input and multi-output device for actuating the 1st (sway) and 2nd (symmetric) in-plane vibration modes. Geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The microcantilever beam in Fig. 1a is modeled as a continuum system through Hamilton’s principle 37 , 38 , yielding the equations of motion below where the boundary conditions and coefficients are expressed in Eqs. (S 16 ) and (S 17a–c) in the Supplementary Materials along with the equation derivation.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The microcantilever beam in Fig. 1a is modeled as a continuum system through Hamilton’s principle 37 , 38 , yielding the equations of motion below where the boundary conditions and coefficients are expressed in Eqs. (S 16 ) and (S 17a–c) in the Supplementary Materials along with the equation derivation.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Most of these studies have demonstrated the M-shaped resonance curve with strong quadratic coupling compared to the Duffing nonlinearity. For instance, U-shaped resonators [31,32], disk resonators [14], arch beam resonators [33], and clamped-clamped beam resonators [20,21,28,34] have experimentally shown Mshaped resonances induced by 1:2 or 2:1 InRes. While these studies have contributed to understanding 1:2 and 2:1 InRes, the ZD point was not demonstrated due to the relatively small hardening effect.…”
Section: Introductionmentioning
confidence: 99%